Strategies to Combat School Dropouts via Digital Technologies: : an experience at IFS-Campus Lagarto - Souza, Fábio Kalil de; Guimarães, Wagner dos Santos; Guedes, Josevânia Teixeira; Alves, Maria José Barreto (Revista Labor, 2021)
It is known that the development of a nation and the insertion and social ascension of the individual go through education, both informal and formal, systematic. In this, the school represents the central locus of formation in Basic Education, and the permanence of the student is a condition for success and continuity of studies in later stages. Otherwise, abandoning or escaping from this space can cause damage to society and to the subject himself. In Brazil, school dropout occurs at different levels and teaching modalities and constitutes one of the main systemic problems faced by governments and educational managers in recent decades. Despite this phenomenon, deepened by the Covid-19 pandemic, causing human and socioeconomic damage, it has been vigorously fought by institutional actions and public policies, although results are not always commendable. This work deals with the search for solutions via technologies to reduce high school dropout in the harsh period of the new coronavirus. Its general objective is only to describe the strategies for coping with school dropout in high school technical education developed by the multidisciplinary team of the IFS-Campus Lagarto using instagram, phone calls, online chat and video calls. As a method, a qualitative descriptive approach was chosen. The study concludes the feasibility and efficiency of psychosocial and pedagogical monitoring through these technologies and points out limits and possibilities for further research.